2018
DOI: 10.3406/mcarh.2018.2057
|View full text |Cite
|
Sign up to set email alerts
|

Sourcing obsidian from prehistoric sites in northwest Romania

Abstract: RALUCA KOGĂLNICEANU-secretar de redacţie RALUCA KOGĂLNICEANU-prelucrare ilustraţie şi aşezare în pagină PIERRE DUPONT (limba franceză), ROXANA DOBRESCU (limba franceză), CLIVE BONSALL (limba engleză), ADINA BORONEANŢ (limba engleză)-consultanţi limbi străine ROMEO CÎRJAN-design copertă www.mcajournal.ro Orice corespondenţă se va trimite Comitetului de redacţie pe adresa: Str. Henri Coandă nr. 11, 010667 Bucureşti, tel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Likewise, at Ohoden in northern Bulgaria dating of the C1 obsidian to the late Starčevo period rests on ceramic typology. Taken together, this evidence is at least consistent with the results of obsidian provenance studies in other regions of Romania that point to preferential use of C1 obsidian throughout Romania from the later stages of the Early Neolithic onwards (Glascock et alii 2017;Boroneanț et alii 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, at Ohoden in northern Bulgaria dating of the C1 obsidian to the late Starčevo period rests on ceramic typology. Taken together, this evidence is at least consistent with the results of obsidian provenance studies in other regions of Romania that point to preferential use of C1 obsidian throughout Romania from the later stages of the Early Neolithic onwards (Glascock et alii 2017;Boroneanț et alii 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Despite the number of Romanian Neolithic sites from which obsidian has been characterised and analysed (Boroneanţ et al 2018(Boroneanţ et al , 2019, the data at present available from Vinča culture and other Middle Neolithic contexts are few (Glasswork et al 2015;Boroneanţ et al 2018). In particular, the detailed study of the Miercurea Sibiului/Szerdahely (Transylvania) lithic assemblages has shown that changes took place in raw material procurement and tool manufacture between the Early (Criş) and Middle (Vinča) Neolithic and Chalcolithic periods, especially as regards the non-obsidian material (Biagi 2015, 257).…”
Section: Discussionmentioning
confidence: 99%